Analysis Damage Pavement Using Binamarga Method On Lamongan-Gresik Road Sta 45+200 - 47+200 - Trio Dimas Pebrianto; Hanie Teki Tjendani; Nurani Hartatik; Yudi Dwi Prasetyo; Eka Dhamayanti (Innovative: Journal Of Social Science Research, 2023)
Lamongan-Gresik road is one of the main roads that is connected to the capital city of East Java Province, Surabaya. This study was conducted to assess damages on the road and to determine the priority level of handling it by conducting a visual survey, pavement surface damage measurement, and LHR survey for one day on the road section. Bina Marga method was utilized in the analysis comprising six types of road damages that are identified, namely: photole, patches, alligator cracking, rutting, reflection cracking, longitudinal and transverse cracks, depression grade, and polished aggregate. The major type of damages is alligator cracking (41.00%) with an area of 792.76 m2, while the minor type of damages is photole (0.08%) with an area of 1.54 m2 from Gresik to Babat, while the major type of damage is alligator cracking by 53.00% with an area of 801.27 m2, and the minor type of damage is reflection cracking by 0.20% with an area of 3.08 m2 from Babat to Gresik. Based on the type of pavement damages reviewed, namely Asphalt (P2), the types of damages that are repaired using local asphalt are alligator cracks, box cracks, longitudinal and transverse cracks with width < 2 mm, and ravelling. Filling the hole (P5) Damages repaired with this method are box cracks, Aligator cracks with crack width > 2 mm and subsidence, and holes > 50 mm deep. Leveling (P6) Damages that need to be repaired by leveling is settlement/subsidence, holes with a depth of 10-50 cm, groove depth < 30 mm.